2013
DOI: 10.1037/a0030391
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy and the combination of psychopathy and sexual deviance as predictors of sexual recidivism: Meta-analytic findings using the Psychopathy Checklist—Revised.

Abstract: Clinicians routinely administer Hare's (2003) Psychopathy Checklist-Revised (PCL-R) to sex offenders and report PCL-R scores as meaningful predictors of recidivism risk. Although a 2005 meta-analysis reported a small (d=0.29) association between PCL-R scores and sexual recidivism (Hanson & Morton-Bourgon, 2005), no meta-analysis has examined effects for PCL-R factors and facets, the widely cited combination of high PCL-R and high sexual deviance scores, or potential moderators of the PCL-R/recidivism relation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 65 publications
5
137
1
5
Order By: Relevance
“…The construct shows relatively high stability across adolescence and into adulthood (Lynam, Caspi, Moffitt, Loeber, & Stouthamer-Loeber, 2007; Lynam, Charnigo, Moffitt, Raine, Loeber, & Stouthamer-Loeber, 2009; Neumann, Wampler, Taylor, Blonigen, & Iacono, 2011). It bears robust relations to antisocial behavior, aggression, substance use, and recidivism (Declercq, Willemsen, Audenaert, & Verhaeghe, 2012; Hawes, Boccaccini, & Murrie, 2013; Neumann, Hare, & Pardini, in press). Recent research has even begun to uncover possible neurobiological underpinnings of psychopathy (Seara-Cardoso & Viding, in press).…”
mentioning
confidence: 99%
“…The construct shows relatively high stability across adolescence and into adulthood (Lynam, Caspi, Moffitt, Loeber, & Stouthamer-Loeber, 2007; Lynam, Charnigo, Moffitt, Raine, Loeber, & Stouthamer-Loeber, 2009; Neumann, Wampler, Taylor, Blonigen, & Iacono, 2011). It bears robust relations to antisocial behavior, aggression, substance use, and recidivism (Declercq, Willemsen, Audenaert, & Verhaeghe, 2012; Hawes, Boccaccini, & Murrie, 2013; Neumann, Hare, & Pardini, in press). Recent research has even begun to uncover possible neurobiological underpinnings of psychopathy (Seara-Cardoso & Viding, in press).…”
mentioning
confidence: 99%
“…In fact, one meta-analytic study found that the predictive power of psychopathy scores was greatly diminished when psychopathy was assessed by retained mental health experts as part of actual forensic assessments, compared to when it was assessed in a research setting where PCL administration and scoring are highly standardized. 32 This and similar findings 33 are concerning because they suggest that mental health experts who testify with regard to violence risk assessment frequently do not have adequate training and do not follow the standard procedure for coding the checklist items.…”
Section: Several Comprehensive Violence Risk Assessment Instruments Hmentioning
confidence: 75%
“…Psychopathic offenders are also more likely to recidivate upon release, often in a violent manner, than nonpsychopathic offenders (Mokros, Vohs, & Habermeyer, 2013;Olver, Lewis, & Wong, 2013;Olver, Stockdale, & Wormith, 2009;Rice & Harris, 2013;Salekin et al, 1996;Yang, Wong, & Coid, 2010). In addition to violence, psychopathic individuals are more likely to engage in persistent sexual offending (e.g., Hanson & Morton-Bourgon, 2005;Hawes, Boccaccini, & Murrie, 2013). The association between psychopathy and violence has also been identified outside of clinical offender samples, where students and general community members scoring higher on psychopathy are more likely to engage in antisocial behaviour than those scoring lower on psychopathy (Walters, 2003a(Walters, , 2003bVitacco, Neumann, & Pardini, 2014).…”
Section: Characteristics Of Psychopathic Personalitymentioning
confidence: 99%